Volunteers' resilience and motivation - Sofia A. Nalichaeva; Anastasia A. Tkachenko; Zinaida V. Borisenko; Bogdan I. Terentyev; Ekaterina M. Lukina (Revista on line de Política e Gestão Educacional)
The relevance of the problem under study is justified by the fact that in the modern world, it is increasingly necessary to ensure maintaining the stability of human life and activity in the circumstances contributing to its destabilization, in the context of a pandemic, the issue of the resilience of volunteers and the motivation of volunteer activities is exceptionally significant. The article aims to describe the results of resilience components' analysis and their correlation with the volunteers' motivation. The top methods in this study are the questionnaire "Adults' resilience", the questionnaire of causal orientations, the author's method of assessing the motivation of volunteer activity. As a result of the study, it was found that if the resilience of volunteers is at a high level, the predominance of self-efficacy indicates that they can mobilize their motivation, cognitive resources, and actions to influence events. During the pandemic, volunteers have been successfully applying mechanisms for organizing situation management, assessment of the effectiveness and results of their efforts, focusing on the meaning of active problem solving, turning to social support, the ability to transform the situation, achieving socially meaningful goals, and effective interaction with the ambient. The main motives of volunteers are a sense of service, compassion, and empathy; many volunteers note the importance of positive emotions, professional experience, and communication. The analysis of correlations between the indicators of resilience and motivation of volunteer activity showed the presence of significant positive correlations; the higher the motivation and interest in volunteer activities, the more developed such components of resilience as coping and adaptation, perseverance, family and social relationships and resilience as volunteers have. The materials of the article can be helpful in psychological support of individual groups of the population and improve psychological literacy, development of resilience in various groups of the population, volunteers, teachers, and psychologists to improve the adaptability and resilience of people who need help. The results can be used in the educational process to train future psychologists and other professionals to increase the motivation for helping activities in students.